Optimization of Breast Milk Production through a Combination of Lactation Acupressure and Swedish Back Massage as a Complementary Nursing Intervention for Postpartum Mothers - A. Sri Ulfi Nofriati; A. Artifasari; Nurhayana Amelia; Gita Pian Ramadani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Abstract Introduction: optimal breast milk production is a key factor in the success of exclusive breastfeeding among postpartum mothers. however, various physical and psychological factors, such as fatigue, stress, and hormonal imbalance, often become barriers to the lactation process. complementary nursing interventions, such as lactation acupressure and swedish back massage, are known to enhance relaxation, improve blood circulation, and stimulate prolactin and oxytocin hormones that play an important role in breast milk production. Objective: to analyze the effectiveness of a combination of lactation acupressure and swedish back massage in optimizing breast milk production among postpartum mothers Method: this study used a quasi-experimental design with a one-group pretest–posttest approach. the sample consisted of postpartum mothers who met the inclusion criteria and were selected using a purposive sampling technique. Results: The statistical analysis using the Wilcoxon Signed Rank Test yielded a p-value of 0.147. Conclusion: The combination of lactation acupressure and Swedish back massage has not been statistically proven to be significant; however, it tends to provide a positive descriptive effect on optimizing breast milk production in postpartum mothers, along with increased relaxation, improved comfort, and reduced breast pain.